Transduction of bacteriophage Mu by bacteriophage T1. - Bendig, M M (1977)
Phage T1 transduces phage Mu PFU from Mu-lysogenic donor cells to sensitive recipient cells. The efficiency of transduction depends on the chromosomal location of the Mu prophage. T1, therefore, appears to package different regions of the bacterial chromosome with different efficiencies. Although T1 transduces bacterial markers with different efficiencies, there is no direct correlation between the efficiency of transduction of a bacterial marker and the efficiency of transduction of Mu PFU from donor cells with the Mu prophage located in that marker.